2022
DOI: 10.3389/fbioe.2022.874742
|View full text |Cite
|
Sign up to set email alerts
|

Green Metallic Nanoparticles: Biosynthesis to Applications

Abstract: Current advancements in nanotechnology and nanoscience have resulted in new nanomaterials, which may pose health and environmental risks. Furthermore, several researchers are working to optimize ecologically friendly procedures for creating metal and metal oxide nanoparticles. The primary goal is to decrease the adverse effects of synthetic processes, their accompanying chemicals, and the resulting complexes. Utilizing various biomaterials for nanoparticle preparation is a beneficial approach in green nanotech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 326 publications
(236 reference statements)
0
60
0
Order By: Relevance
“…And liposomal DOX is currently approved by the Food & Drug Administration (FDA) [ 80 ]. More recently, researchers combined the Se@SiO 2 nanocomposite and DOX, from which they discovered the promising effect of Se@SiO 2 against ACT [ 81 , 82 ]. Besides, clinicians found that the slower continuous infusion dosing of ANTs could reduce the risk of cardiotoxicity compared with the rapid bolus dosing [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…And liposomal DOX is currently approved by the Food & Drug Administration (FDA) [ 80 ]. More recently, researchers combined the Se@SiO 2 nanocomposite and DOX, from which they discovered the promising effect of Se@SiO 2 against ACT [ 81 , 82 ]. Besides, clinicians found that the slower continuous infusion dosing of ANTs could reduce the risk of cardiotoxicity compared with the rapid bolus dosing [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doping TM in oxides raises the crystal defect and modifies the optical band by changing the absorbance to a higher wavelength [ 10 ]. Zinc oxide (ZnO) is a potential photocatalytic material with a band gap of 3.4 eV [ 11 , 12 ]. ZnO NPs are being investigated as a catalyst for the degradation of organic contaminants due to their high crystallinity, greater surface activity, and microstructural characteristics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various researchers have reported on nanotechnology and its influence on pharmaceutical development, as well as metallic nanoparticles and their wide variety of potentials in pharmaceutical applications such as antiparasite, bactericidal, anti-cancer, fungicidal, and so on. ( Chopra et al, 2022 ). published a systematic assessment of the efficacy of these nanoparticles (NPs) against lung cancer using in vitro models (2019).…”
Section: Fungal Nanobiotechnologymentioning
confidence: 99%